Optimization of molding parameter effect to warpage and shrinkage of laboratory goggle based on plastic flow simulation software - Mohd 'Afif, Abd Aziz (2010)
This thesis is about how to optimization of molding parameter effect to warpage and shrinkage. The product that will be use is laboratory goggle. The objective of this thesis is to analyze the parameters effect in injection molding to warpage and shrinkage of laboratory goggle and to determine the optimization of molding parameter effect to warpage and shrinkage of laboratory goggle during injection molding based on plastic flow simulation software. The thesis describes the moldflow software how to analyze frame and glass of laboratory goggle to identify the parameter effect to warpage and shrinkage of the product .. It need to scanning the frame and the glass of laboratory goggle and it need to use a 3D scanner machine. Then, transfer the shape and result to the solidwork software and find the dimension of the frame and glass to draw a new shape using solidwork software. Next, import the frame and glass from solidwork to the moldflow software and analyze the product. Make a optimization of the product from warpage and shrinkage. In this project, parameter in injection molding of laboratory goggle needs to define. The parameter includes mold temperature, melt temperature, injection time, and packing pressure. According to result from moldflow software, in conclusion the factor that influence the molding process it is pressure, temperature, molding temperature, molding cool must be in a correct position because it will be give a effect if the factor is not suitable.